Sustaining Trade Reform : Institutional Lessons from Peru and Argentina - Baracat, Elías A. (World Bank, Washington, DC, 2014)
This paper examines trade policies in Peru and Argentina since the reforms of the 1990s. Peru provides a valuable example of sustaining reform. Leaders have used negotiations and other international instruments to disseminate among Peruvians a positive vision of Peru in the international economy and to extend the application of World Trade Organization-based governance principles. Peru has introduced few new restrictions and all of them have been through World Trade Organization-sanctioned policy instruments. Argentina, by contrast, has introduced multiple restrictions, through procedures that eschew World Trade Organization governance principles. Moreover, leaders there have returned trade politics to the dependencia philosophy that sees the international economy as an exploitive environment. The paper brings out the weakness of international obligations to limit Argentina's return to import substitution and the pains at which Peru has gone to maintain the management of its economy within the same rules that Argentina has so easily violated.